We Built It, Now Will They Come? bOK Systems Corp. - Ensign, Prescott C.; Mirzaee, Aydin Y. (Senate Hall, 2015)
bOK Systems Corp., a Canadian-based start-up, has been able to launch its product in the market but is looking to take it to the next level and increase the adoption of its service amongst the masses. The venture team is facing challenges such as a shortage of time and money. A dilemma is that time and money are substitutes; chasing capital takes the focus away from other areas that need attention. Raising funds for the venture is not easy given the lacklustre investment environment in Canada. The team is now considering multiple alternatives, such as focusing full time on bOK (i.e., quitting all other efforts), bringing in an external CEO, or liquidation and exit. Keywords: technology-based enterprise, high potential, high risk, new venture financing, leadership, vision
Keywords: technology-based enterprise|high potential|high risk|new venture financing|leadership|vision